(untitled) (Physical Education, Health and Social Sciences, 2025)
Mosquitoes (Diptera: Culicidae) are major vectors of several life-threatening diseases, including dengue, malaria, and filariasis, posing significant challenges to global public health. Understanding their species composition and diversity is critical for implementing effective control strategies. The present study aimed to investigate the diversity, relative abundance, and distribution of mosquito species in District Narowal, Punjab, Pakistan. The survey was conducted from November 2023 to April 2024 across 24 Union Councils of District Narowal. Mosquito adults, larvae, and pupae were collected using standard entomological techniques, including mouth aspirators, sweep nets, knockdown methods, and dipping. Specimens were identified morphologically using standard taxonomic keys. A total of 1,050 mosquitoes were recorded, representing 13 species across five genera: Culex, Aedes, Anopheles, Armigeres, and Mansonia. Culex quinquefasciatus was the most abundant species (50.76%), followed by Cx. perexigus (15.52%) and Cx. fuscocephala (13.24%). Ae. albopictus and Ar. obturbans were the least abundant (0.38%). Species diversity, based on Shannon index, was highest in Bari Minhassan and Talwandi Binderan (H = 1.83) and lowest in Nainakot (H = 0.63). The findings underscore the predominance of Culex species and the presence of multiple disease vectors, highlighting the need for integrated vector management strategies in Narowal. Further research on seasonal variation, insecticide resistance, and molecular identification is recommended to strengthen vector control programs.